Association of dietary sodium:potassium ratio with the metabolic syndrome in Chinese adults. Issue 6 (2nd August 2018) - Li, Xiaocheng; Guo, Baofu; Jin, Di; Wang, Yanli; Jiang, Yun; Zhu, Baichun; Chen, Yang; Ma, Liankai; Zhou, Han; Xie, Guoxiang
Abstract: Several epidemiological studies have investigated that Na or K intakes might be associated with the metabolic syndrome (MetS). However, little evidence has evaluated the association between Na:K ratio and the MetS. In this study, we assessed the association between the dietary Na:K ratio and the MetS. The cross-sectional study was conducted among adults aged 18 years and older in Nanjing, using a multi-stage random sampling method, which resulted in a sample size of 1993 participants. Dietary Na and K intakes were assessed by 3 consecutive days of dietary recollection combined with condiments weighing method. Health-related data were obtained by standardised questionnaires, as well as physical examinations and laboratory assessments. The prevalence rate of the MetS was 36·5 % (728/1993). After adjusting for various lifestyle and dietary factors of the MetS, participants in the highest quartile of dietary Na:K ratio were at a higher risk of developing MetS (OR=1·602; 95 % CI 1·090, 2·353) compared with those in the lowest quartile. Each 1-sd increase in dietary Na:K ratio was associated with a higher risk of prevalent MetS (OR=1·166; 95 % CI: 1·018, 1·336). Among the components of the MetS, dietary Na:K ratio was positively associated with high blood pressure (quartile 3 v . quartile 1: OR=1·656; 95 % CI 1·228, 2·256) and hypertriacylglycerolaemia (quartile 4 v . quartile1: OR=1·305; 95 % CI 1·029, 1·655) in multivariate analysis. These results revealed that higher dietary Na:K ratio significantly increased the risk of the MetS in Chinese adults. Further studies are needed to verify this association.